2014
DOI: 10.3389/fpsyg.2014.00104
|View full text |Cite
|
Sign up to set email alerts
|

Rationality and the illusion of choice

Abstract: The psychology of reasoning and decision making (RDM) shares the methodology of cognitive psychology in that researchers assume that participants are doing their best to solve the problems according to the instruction. Unlike other cognitive researchers, however, they often view erroneous answers evidence of irrationality rather than limited efficiency in the cognitive systems studied. Philosophers and psychologists also talk of people being irrational in a special sense that does not apply to other animals, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It has been suggested that it is System 1 that is in use when any of the reasoning heuristics are being utilised, and can be seen to be using intuition, while System 2 is held to utilise, and be limited by, working memory resources to make more 'rational choices. It is also clear that while heuristics are, by definition, short cuts in reasoning, this does not mean that they lead to inaccurate or unhelpful judgements in all situations (see for instance Hogarth & Karelaia, 2006;Evans, 2014, Mandel 2014.…”
Section: Dual Process Theories Of Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that it is System 1 that is in use when any of the reasoning heuristics are being utilised, and can be seen to be using intuition, while System 2 is held to utilise, and be limited by, working memory resources to make more 'rational choices. It is also clear that while heuristics are, by definition, short cuts in reasoning, this does not mean that they lead to inaccurate or unhelpful judgements in all situations (see for instance Hogarth & Karelaia, 2006;Evans, 2014, Mandel 2014.…”
Section: Dual Process Theories Of Reasoningmentioning
confidence: 99%
“…As such, the fact that the frequency format led to less overestimation is an indication that it aids reasoning. Evans (2014) states that the research in this field should move away from categorising responses, and people, as being either 'rational' or 'irrational', and Mandel (2014) also suggests that there needs to be "better discussion of whether being non-Bayesian is necessarily irrational" (p3). Moving the focus towards degrees of accuracy, rather than absolutes, is following this trend in suggesting that the aim should be in moving towards reasoning that is functional, and advantageous to the individual.…”
Section: Measures Of Reasoning: Normal and Natural Frequencies 41mentioning
confidence: 99%
“…In this perspective, it may happen to discover that laypeople are often not rational in evaluating arguments, thus breaking normative ties and systematically falling into argumentation fallacies ( Van Eemeren, 1992 ; Ariely, 2008 ; Walton, 2010 ). As pointed out by Jonathan Evans (2014) , this does not mean that agents are (completely) irrational, as often claimed in psychology of reasoning and decision making ( Wason, 1966 ; Wason and Johnson-Laird, 1972 ). This work attempts to suggest that they might simply be creative in argumentation, finding alternative reasons to make sense of their own conclusions and evaluations.…”
Section: Introductionmentioning
confidence: 98%
“…Jonathan St. B. T. Evans, in his engaging article “Rationality and the illusion of choice” (Evans, 2014 ) argues that erroneous answers to questions posed in the study of reasoning and decision-making (RDM) ought not be viewed as irrational , just as errors in other cognitive domains are not viewed as irrational. He attributes misuse of the term partly to use of normative models borrowed from economics or mathematics but even more to an RDM assumption of conscious, controlled rationality.…”
mentioning
confidence: 99%
“…Evans ( 2014 ); Evans (paragraph 12) writes: “How can we both presuppose rationality and then infer irrationality from errors? Researchers in no other fields of cognitive psychology do this, inferring instead cognitive limitations from errors.” Thus, perceptual inaccuracy is described using language of perceptual illusion; suboptimal memory performance is forgetting or distortion.…”
mentioning
confidence: 99%